An Algorithm of Digital Image Interpolation - Minasyan, Lilit G. (Mathematical Problems of Computer Science, 2021)
The effective algorithms for reducing and increasing the size of images using the orthogonal wavelet-like transformation are presented. The experimental results show an improvement in terms of PSNR in comparison to the well-known image interpolation algorithms.